Artistic activity and its role in the aesthetic response of middle school students (Al-Academy, 2025)
Artistic activities are one of the most prominent types of arts in which the learner can express his feelings and emotions. These activities include various fields, including the art of drawing, design, and other artistic fields that contribute to building the learner’s personality from all psychological, mental, emotional, and social aspects. At the top of these aspects is the aesthetic aspect, which is not  It is less important than the aspects that preceded it. Transforming material objects into feeling and feeling indicates the awareness of aesthetic values, as the aesthetic response aims to develop an awareness of the foundations and relationships in artistic composition so that the learner becomes a connoisseur of beauty, and from here there becomes an urgent need to educate the learner to sense beauty, taste it, and respond to it, through which the learner acquires the characteristics of his aesthetic development.  Its effects are reflected on his environment and society. The research included four chapters. In the first chapter, the researcher addressed the research problem, which lies in answering the question: Does artistic activity have a role in the aesthetic response of middle school students?The researcher touched on the importance of the research as it contributes to enriching the learner’s personality and developing it in its cognitive, emotional, and skill aspects. The aim of the research is to identify artistic activity and its role in the aesthetic response of middle school students. The second chapter included two sections. The first section was titled Artistic Activity, in which the researcher explained the importance of artistic activity for the learner. The second section was titled Aesthetic Response, in which the researcher addressed the importance, goals, and foundations of aesthetic response. As for the third chapter, the research population included the total number of students affiliated with the Ministry of Education, Baghdad Directorate of Education, Al-Karkh I, Al-Mutamayzin Al-Khadra Secondary School for Boys - Fifth Grade of Middle School. As for the research sample, it was chosen randomly because the community was homogeneous, and its number reached (20) students who were chosen from the research community.For the purpose of achieving the goal, the researcher adopted a tool to measure aesthetic response, which is the CRAFTS scale, and the researcher carried out validity and reliability measures on it. The results showed that artistic activity has a role in aesthetic response through the post-test of the scale.  The researcher concluded conclusions including: That artistic activity has a role in aesthetic response and bringing about positive change in this field, and this is what the current study confirmed and through the results it reached, and based on the conclusions reached by the current research, the researcher recommends: Including the Aesthetic Response Scale (CRAVS) in the art education teacher’s guide.At the end of her research, the researcher proposes to conduct a comparative study between the College of Fine Arts and Basic Education in the aesthetic response to the foundations and relationships in artistic composition.